Determinants of Dividend Pay-Out Policy of Listed Non-financial Firms in Malaysia - Tahir, Hussain; Masri, Ridzuan; Rahman, Mahfuzur (Sciedu Press, 2020)
This research paper scmtinizes to recogoize the detemiinants of dividend pay-out. A total of 203 Malaysian non-fiiiancial firms representing from various iiidustries were scrutinized over a period of foiirteen fiiiancial years covering 2005 to 2018. The panel data forni specified the tiine series and cross-sectiooal nature used for this research paper. Fixed effect and randoni effects description techniques were used for investigation. The outcomes reveal a statistically significant and positive association between coiporate board size. ROA and dividend pay-out. However. financial leverage has a negative and significant relationship with dividend policies. But the study reveals a statistically insignificant and positive relationship between board diversity and dividend pay-out. This paper suggestions insiglit to policy-makers of emerging econoniies interested in the developnient of the financial structure niechanism. This study guides companies in the structure and employnient of dividend pay-out. © 2020 Sciedu Press.